Meningkatkan Kualitas Pelayanan Publik Melalui Inovasi MARI-SERBU di Kecamatan Sukodono, Sidoarjo - Syahrani, Regita Pinkan; Wahyudi, Kalvin Edo (Petanda: Jurnal Ilmu Komunikasi dan Humaniora, 2025)
The MARI-SERBU (Malam Hari Senin Rabu) innovation in Sukodono District, Sidoarjo, is a public service that operates in the evening, specifically on Mondays and Wednesdays from 6:00 PM to 8:00 PM. This program, managed by the District Office, provides services for managing population administration. This innovation offers a solution for people who are busy during regular working hours, allowing them to take care of their population documents. This study aims to describe the implementation of the "MARI-SERBU" population service innovation in Sukodono District, Sidoarjo, using Rogers' Innovation Theory, which includes relative advantage, compatibility, complexity, trialability, and observability. The results of this study indicate that the MARI-SERBU service innovation in Sukodono District benefits the community by allowing them to manage population administration at night. Furthermore, this innovation has successfully met four indicators of innovation: relative advantage, compatibility, complexity, and trialability. However, the observability indicator has not yet been fully achieved, as some community members are still unaware of the MARI-SERBU innovation due to insufficient information dissemination in physical form by the Sukodono District Office, Sidoarjo.